The Effects of Specific and Ad Valorem Taxes - Bishop, Robert L. (Quarterly Journal of Economics, 1968)
Introduction, 198. — I. Specific tax, 198. — II. Ad valorem tax, 202. — III. Comparisons of specific and ad valorem taxes, 204. — IV. Tax burdens, 208; pure competition with pecuniary external diseconomies, 209; pure competition with real external diseconomies, 212; monopoly with fixed factor, 213; monopoly plus monopsony, 215; monopoly with other internal disecono|mies, 216; other cost and supply patterns, 217.